The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/13670050.2011.560931
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for enrollment at a Spanish–English two-way immersion charter school among highly motivated parents from a diverse community

Abstract: This study builds on previous work to examine parent reasons for enrolling their children in a two-way immersion (TWI) charter school. This work goes beyond ethno linguistic background variables (language, ethnicity), to include other key variables such as education level, income, religion, household distance from school, and family structure. This study takes place in one school-wide TWI program in a charter school where parents must choose and actively pursue enrollment. These highly motivated parents articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
(11 reference statements)
0
11
0
2
Order By: Relevance
“…Second, published studies that examined the reasons behind parents' choice of a dual‐immersion program for their children have consistently revealed that the primary reasons cited by the parents are the desire for the children to become bilingual, and future benefits for educational and career opportunities envisioned as the result of dual‐immersion programs (e.g. Gerena, ; Parkes, ; Whiting & Feinauer, ), rather than any particular talent for language learning that they observe in their children. Third, in the present study, we observed differences between the two groups of children on very specific measures rather than across the board.…”
Section: Resultsmentioning
confidence: 99%
“…Second, published studies that examined the reasons behind parents' choice of a dual‐immersion program for their children have consistently revealed that the primary reasons cited by the parents are the desire for the children to become bilingual, and future benefits for educational and career opportunities envisioned as the result of dual‐immersion programs (e.g. Gerena, ; Parkes, ; Whiting & Feinauer, ), rather than any particular talent for language learning that they observe in their children. Third, in the present study, we observed differences between the two groups of children on very specific measures rather than across the board.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that a variety of different psychological and sociocultural factors may influence the nature of involvement in this setting and that parental involvement in such a context thus merits study in its own right. Recently, the role of parents in dual immersion has received some research attention, with Whiting and Feinauer (2011) examining parents' motivations for choosing dual immersion and Parkes and Tenley (2011) looking at parents' satisfaction with dual language programmes. While such analyses of parental motivation and satisfaction are important in enlarging our understanding of the role of parents in immersion, it is argued that it is crucial that an exploration of why and how parents are actually involved once they have chosen immersion is particularly important in order to help secure student success in these programmes.…”
Section: Parental Involvement In Immersionmentioning
confidence: 99%
“…Future career opportunities were another benefit of bilingualism reported by parents (Whiting & Feinauer, 2011). Being bilingual, biliterate, and bicultural was viewed as a means to more career opportunities, a view expressed by both language minority and language majority parents.…”
Section: Benefits Of Bilingualismmentioning
confidence: 99%
“…(Whiting & Feinauer, 2011, p. 643) Another benefit of participation in bilingual programs in school was that the students learned about diversity and other cultures on a daily basis as they studied in both languages. A final benefit for the EL students as reported by their parents was that they were able to retain their heritage by learning their native language in an academic setting (Whiting & Feinauer, 2011).…”
Section: Benefits Of Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation